Adjuvant chemotherapy for gastric cancer - I. P. Kolesnyk; A. I. Shevchenko (Zaporožskij Medicinskij Žurnal)
Gastric cancer remains one of the most interesting problem of the oncology. Combined approach is recommended for treatment of gastric cancer patients and it use almost in all countries of the world. The role of adjuvant chemotherapy for patients with gastric cancer discusses since the mid of XX century.